Fatigue and rapid hamstring/quadriceps force capacity in elite soccer players - Greco, C.; Silva, W. L.; Camarda, S. R.; Denadai, B. S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Muscle fatigue, defined as a reduction in the maximal force exerted by a muscle or a muscle group due to central and/or peripheral mechanisms is frequently found during soccer match, especially towards the end of play. Significant changes in the conventional concentric hamstrings:quadriceps ratio (Hcon:Qcon) and functional eccentric hamstrings:concentric quadriceps ratio (Hecc:Qcon) were also found after both exhaustive laboratory-based soccer-specific exercise and a field test representative of soccer specific movements. Zebis et al. (2011) have recently introduced the rate of force development (RFD) hamstrings:quadriceps strength ratio (RFDH:Q) to assess the potential to stabilize the knee joint during explosive movements of elite soccer players. Thus, the aim of this study was to investigate the effect of fatigue induced by an exhaustive laboratory-based soccer-specific exercise on different hamstrings:quadriceps (H:Q) ratios of soccer players. Methods: Twenty-two male soccer players (23.1±3.4 yr.) performed maximal eccentric and concentric contractions for knee extensors (KE) and flexors (KF) at 60°/s and 180°/s to assess Hcon:Qcon and Hecc:Qcon ratios. Additionally, they performed maximal voluntary isometric contractions for KE and KF, from which the maximal muscle strength, RFD and RFDH:Q were extracted. Thereafter, subjects performed an exhaustive laboratory-based soccer-specific exercise and a post-test similar to the pre-test. Results: There was significant reduction of Hcon:Qcon (0.60±0.06 vs. 0.58±0.06) and Hecc:Qcon (1.29±0.2 vs. 1.16±0.2) after the soccer-specific exercise. However, no significant difference between Pre and Post exercise conditions was found for RFDH:Q at 0-50 (0.53±0.23 vs. 0.57±0.24) and 0-100 ms from the onset of muscle contraction (0.53±0.17 vs. 0.55±0.17). Discussion: The principal original finding of this study was that the H:Q strength ratios based on peak force values are more affected by fatigue induced by a soccer specific intermittent protocol than rapid H:Q force capacity. The reduction of both Hcon:Qcon and Hecc:Qcon is consistent with previous studies (Rahnama et al., 2003; Delextrat et al., 2010). RFDH:Q obtained during early contraction phase was not modified after exercise. Thus, fatigue induced by soccer specific intermittent protocol seems not reduce the potential for knee joint stabilization during the initial phase of voluntary muscle contraction.